Economic Integration and Manufacturing Location in EU Accession Countries - Simonetta Longhi; Peter Nijkamp; Iulia Traistaru (Tinbergen Institute, 2003)
This paper investigates patterns of manufacturing location in the context of increased economic integration in Central and East European countries. Using regional data for the period 1990-1999, we identify and compare patterns and determinants of manufacturing location in five European Union (EU) accession countries: Bu1garia, Estonia, Hungary, Romania and Slovenia. Our research results suggest that, in these countries, regiona1 relocation of industries has taken place, leading in Bulgaria and Romania to increasing regional specialization. However, regional specialization has not changed significant1y in Estonia, Hungary and Slovenia. We find empirical evidence indicating that both factor endowments and geographic proximity to largemarkets determine the location of manufacturing in EU accession countries.
Keywords: F15; R11; R12; P52; 330; Economic integration; manufacturing specialization; geographical concentration of industries; EU accession countries; Betrieblicher Standort; Betriebliche Standortwahl; Regionales Cluster; Europäische Integration; Industrie; EU-Mitgliedschaft; Osteuropa